2017
DOI: 10.1039/c6en00567e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gold nanoparticles on extracellular nutrient-cycling enzyme activity and bacterial community in soil slurries: role of nanoparticle size and surface coating

Abstract: Engineered nanoparticles such as gold that are considered to be relatively chemically inert can influence soil enzyme activities and the composition of microbial communities that play an important role in nutrient cycling and soil health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…Lower toxic effects for nano from in some samples may have been determined by their tendency to aggregation and solubility. Aggregation causes a decrease of specific surface area of nanoparticles and of their solubility, and hence, lowers reactivity [19,20]. Similar conclusions were obtained by Kim et al (2011) who also observed different dehydrogenase activity in the presence of the nano-than the bulk form of CuO [9].…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Lower toxic effects for nano from in some samples may have been determined by their tendency to aggregation and solubility. Aggregation causes a decrease of specific surface area of nanoparticles and of their solubility, and hence, lowers reactivity [19,20]. Similar conclusions were obtained by Kim et al (2011) who also observed different dehydrogenase activity in the presence of the nano-than the bulk form of CuO [9].…”
Section: Resultssupporting
confidence: 76%
“…We also observed (after 24 h in high tested concentration) inhibition cellular respiration in TTC method [19].…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Similar effects were observed with TiO 2 NPs (15-20 nm diameter), 164 CuO NPs (<50 nm) 165 and Au NPs (50 nm size). 166 Fe 3 O 4 NPs (10.2 ± 2.6 nm diameter) deteriorated the mutual interaction between arbuscular mycorrhizal fungi and maize, negatively affecting plant biomass and carbon accumulation and P cycling in the soil. 167 Likewise, Ag NPs (20.4 ± 3.2 nm) caused similar effects, generating plant growth inhibition and decreased root mycorrhizal colonization rate.…”
Section: Effects Of Nanoparticles In Soil and Soil Microbiotamentioning
confidence: 99%
“…In the present study, it was revealed that dehydrogenase activity is less sensitive to contamination by Cu, Zn, and Ni NPs than catalase activity. Previous studies have shown both the negative impact of NPs on the activity of enzymes (Kolesnikov, Timoshenko, et al, 2021;Peyrot et al, 2014;Shende et al, 2021) and the positive effect (Asadishad et al, 2017).…”
Section: Discussionmentioning
confidence: 99%